![](https://rs.olm.vn/images/avt/0.png?1311)
- \(\left(2x+5\right)^2=\left(x+2\right)^2\Leftrightarrow\left(2x+5+x+2\right)\left(2x+5-x-2\right)=0\)\(\Leftrightarrow\left(3x+7\right)\left(x+3\right)=0\Leftrightarrow\orbr{\begin{cases}x=-\frac{7}{3}\\x=-3\end{cases}}\)
- \(x^2-5x+6=0\Leftrightarrow x^2-6x+x-6=0\Leftrightarrow x\left(x-6\right)+\left(x-6\right)=0\)\(\left(x+1\right)\left(x-6\right)=0\Leftrightarrow\orbr{\begin{cases}x=6\\x=-1\end{cases}}\)
- \(2x^3+6x^2=x^2+3x\Leftrightarrow2x^2\left(x+3\right)=x\left(x+3\right)\)\(\Leftrightarrow\left(x+3\right)\left(2x^2-x\right)=0\Leftrightarrow x\left(2x-1\right)\left(x+3\right)=0\Leftrightarrow\)\(x=0\)hoặc \(x=\frac{1}{2}\)hoặc \(x=-3\)